2016
DOI: 10.1177/1932296816639069
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Use of Glucose Rate of Change (ROC) Arrows to Adjust Insulin Therapy Among Individuals With Type 1 and Type 2 Diabetes Who Use Continuous Glucose Monitoring (CGM)

Abstract: In 2013, we surveyed 300 individuals with T1D and insulin-treated T2D to assess how they are using real-time CGM and responding to their glucose information in real-world settings. Our subsequent report presented findings regarding CGM data utilization behaviors among the 222 T1D individuals who used real-time CGM and responded to the survey. 11 In a subsequent analysis, we reported differences in use of ROC arrows, comparing T1D respondents treated with continuous subcutaneous insulin infusion (CSII) versus m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 20 publications
0
27
0
Order By: Relevance
“…Recent surveys indicate that people with diabetes using rtCGM rely on trend arrows to calculate mealtime insulin boluses and also to make corrective insulin dose adjustments between meals [31]. Importantly, in response to RoC trend arrows, respondents using rtCGM made significantly larger dose adjustments than would be recommended by published algorithms for using RoC trend arrows for insulin dose management [32,33].…”
Section: Trend Arrows and Insulin Dosing Decisionsmentioning
confidence: 99%
“…Recent surveys indicate that people with diabetes using rtCGM rely on trend arrows to calculate mealtime insulin boluses and also to make corrective insulin dose adjustments between meals [31]. Importantly, in response to RoC trend arrows, respondents using rtCGM made significantly larger dose adjustments than would be recommended by published algorithms for using RoC trend arrows for insulin dose management [32,33].…”
Section: Trend Arrows and Insulin Dosing Decisionsmentioning
confidence: 99%
“…17,18 However, a recent survey of 300 individuals with type 1 and type 2 diabetes using RT-CGM found that those initial recommendations of 10-20% adjustments in doses are viewed as too conservative (Table 2 and Table 3). [19][20][21] From that survey it is clear that for extreme trends people with diabetes are inclined to take more drastic action than were initially recommended, and that individuals using multiple daily injections of insulin make even larger changes (correction and mealtime) compared to pump users. An adjustment in the timing of mealtime insulin relative to the meal based on the ROC was reported by most (58%) of the type 1 respondents including MDI-treated (61%) and CSIItreated (58%) and most of the type 2 respondents (67%).…”
Section: Abbott Freestyle Librementioning
confidence: 99%
“…No systematic evaluations have been reported on the information most often used in daily life to guide insulin adjustment decisions, i.e., whether individuals with diabetes mostly rely for decisions on insulin dose adjustment on the current glucose value, the glucose profile over the previous few hours, or the "trend arrow" (which indicates when the blood glucose is rapidly falling or rising but differs in format between devices) (44,45) [3e].…”
Section: Data Handling and Reportingmentioning
confidence: 99%